A Pilot Study of Using Smartphone Application vs. Routine Follow-Up for Patient Care in Advanced Non-Small Cell Lung Cancer During the COVID-19 Pandemic Era - Prasongsook, Naiyarat; Seetalarom, Kasan; Saichaemchan, Siriwimon; Udomdamrongkul, Kittipong (Frontiers in Medical Technology, 2022)
Introduction: The monitoring of cancer care should be adopted regarding the COVID-19 pandemic preparedness plan. Lung Cancer Care application was a mobile application program for adverse events monitoring and reporting outcomes. This study aimed to invent a new mobile application evaluating PRO for NSCLC patients and to evaluate the validity of mobile application in the COVID-19 pandemic era particularly. Methods: The validity of the application was tested. FACT-L questionaries were contained in the mobile application-based PRO. Patients were randomly assigned to use mobile application-based PRO versus routine follow-up. The primary endpoint was to compare the quality of life (QoL) score between the two groups. The secondary endpoint was OS, and outcome of progressive disease (PD) between 2 groups. Results: Thirty-three patients with advanced NSCLC were enrolled. Patients with the mobile application group had more FACT-L scores at 3 months than patients with routine follow-up arm (106 ± 5.97 vs 99.96 ± 5.74, p-value = 0.07). The median follow-up time was 5.43 months, patients with mobile applications had longer median OS than patients with routine follow up (4 months vs 2.9 months, p-value = 0.5). The sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of this application for predicting disease progression were 50%, 83.3%, 66.7%, and 70% respectively. Conclusion: Self-reported symptoms by Lung Cancer Care application improved quality of life and was similar monitoring outcomes to face-to-face follow up. This tool is applicable for cancer patients as safe as possible for physical distancing in the COVID-19 pandemic era.